2009
DOI: 10.1016/j.jdent.2009.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium, amine and stannous fluoride at the same concentration and different pH on in vitro erosion

Abstract: Effect of sodium, amine and stannous fluoride at the same concentration and different pH on in vitro erosion Abstract OBJECTIVE: This study aimed to compare the effects 0.5% and 1% sodium, amine and stannous fluoride at different pH on enamel erosion in vitro. METHODS: Bovine enamel samples were submitted to a cyclic de-and remineralisation for 3 days. Each day, the samples were exposed for 120 min to pooled human saliva and subsequently treated with one of the fluoride solutions for 3 min: amine fluoride (AmF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
2
20

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 24 publications
0
50
2
20
Order By: Relevance
“…This is possibly because the precipitates formed by application of native AmF had less solubility in citric acid thus providing a protective barrier to conventional glassionomer cement and polyacid-modified resin composite surface against erosive attack 3) . Further, the surfactant properties of AmF might contribute to its superior erosion-prohibiting potential compared to other fluoride measures 33) .…”
Section: Fig 1 Representative Sem Images Of Dyract Extra (15000×)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is possibly because the precipitates formed by application of native AmF had less solubility in citric acid thus providing a protective barrier to conventional glassionomer cement and polyacid-modified resin composite surface against erosive attack 3) . Further, the surfactant properties of AmF might contribute to its superior erosion-prohibiting potential compared to other fluoride measures 33) .…”
Section: Fig 1 Representative Sem Images Of Dyract Extra (15000×)mentioning
confidence: 99%
“…Generally speaking, the strategy of the fluoride application is to render the tooth tissue more resistant against acid attacks 1) . In literature, a number of studies showed that fluoride application is able to reduce erosive substance loss, calcium release, and surface softening of enamel and dentine [2][3][4][5][6][7] . Overall, although clinical studies regarding the erosion-inhibiting potential of fluoridation are not yet available, the protective effect of fluoride application on erosion progression have been shown both in vitro and in situ.…”
Section: Introductionmentioning
confidence: 99%
“…The de-/remineralization cycle was performed in a so-called artificial mouth 13 allowing alternating erosion and remineralization of the specimens under standardized conditions in chambers, which are connected to two multichannel pumps (acid solution and artificial saliva). The specimens were subjected to the artificial mouth for 3 days with six erosive attacks daily.…”
Section: Methodsmentioning
confidence: 99%
“…Dentre eles, preparações contendo estanho associado a fluoretos provaram ser muito eficazes na redução da desmineralização erosiva (Ganss et al 2004(Ganss et al , 2008(Ganss et al , 2010a(Ganss et al , 2010b(Ganss et al , 2012b(Ganss et al , 2014(Ganss et al , 2015Schlueter et al, 2009aSchlueter et al, , 2009bSchlueter et al, , 2009cSchlueter et al, , 2009dSchlueter et al, , 2009e, 2010Schlueter et al, , 2011aSchlueter et al, , 2013Schlueter et al, , 2014Hove et al, 2006Wiegand et al, 2009;Yu et al, 2010aYu et al, , 2010bComar et al, 2012;Huysmans et al, 2011;Stenhagen et al, 2013;Rakhmatullina et al, 2013;Lussi, 2014).…”
Section: Mecanismo De Ação Dos Fluoretosunclassified
“…Estudos in vitro (Sorvari et al, 1994;Büyükyilmaz et al, 1997;Ganss et al, 2001;vanRijkom et al, 2003;Vieira et al, 2005;Hove et al, 2006;Lagerweij et al, 2006;Schlueter et al, 2007;Ganss et al, 2008;Wiegand et al, 2009;Yu et al, 2010a,b) e in situ (Ganss et al, 2004;Schlueter et al, 2009aSchlueter et al, , 2011aWiegand et al, 2010a;Mathews et al, 2012) mostraram a eficácia de diferentes produtos fluoretados na proteção e remineralização de lesões de erosão em esmalte dental. A maioria destes estudos avaliou compostos fluoretados utilizados que apresentam eficácia comprovada na prevenção e controle da cárie dental, como fluoreto de sódio (NaF), fluoreto de amina (AmF), fluoreto de estanho (SnF 2 ) e tetrafluoreto de titânio (TiF 4 ), os quais apresentam diferentes interações com o tecido mineralizado dental.…”
Section: Introductionunclassified